Community Empowerment through CSR-Based STEM Project Expo in Advancing Clean Energy Literacy - Sukmayadevi (Prospect Publishing, 2026)
The transition toward clean energy has become a global priority in addressing climate change and increasingly complex energy challenges. The education sector plays a crucial role in strengthening students' energy literacy and sustainability awareness through contextual and experiential learning approaches. This community service program aimed to analyze the implementation of the Energy Independent School Program as a community empowerment initiative by integrating Corporate Social Responsibility (CSR) with practice-based learning and the STEM Project Expo. The program was implemented using a collaborative community empowerment approach involving multiple stakeholders through the identification of school needs and potential, the provision of renewable energy infrastructure as a contextual learning medium, STEM-based training and mentoring, project-based learning implementation, and participatory monitoring and evaluation. The implementation results demonstrated that collaboration between industry and higher education institutions successfully integrated renewable energy infrastructure with project-based learning, enabling students to develop innovative projects and learning modules that were presented at the STEM Project Expo. This approach helped improve students' energy literacy, creativity, and collaborative skills. The findings indicate that integrating CSR, project-based learning, and multi-stakeholder collaboration is a promising approach to supporting sustainable energy education.